The effects of orally ingested Delta-9-Tetrahydrocannabinol on drivers' hazard perception and risk-taking behaviours: A within-subjects study of medicinal cannabis users. - Mieran, Taren; Hill, Andrew; Horswill, Mark S.; Summers, Mathew J.; Stefanidis, Kayla B. (Psychopharmacology, 2026)
Medicinal cannabis use is increasing worldwide, yet its impacts on driving safety in frequent users are not clearly understood. A more comprehensive understanding of the effects of THC on driving behaviour in frequent users is needed to guide drug driving policy and evidence-based advice for medicinal cannabis consumers. This study investigated the acute effects of orally ingested THC oil on medicinal cannabis users': (a) hazard perception skill performance; (b) driving-related risk-taking behaviours (speeding propensity, following distance, gap acceptance); (c) self-perceived hazard perception skill performance; and (d) self-perceptions of driving skills and safety. A within-subjects design was used to compare scores on validated video-based measures of hazard perception skill and risk-taking behaviours, along with self-report measures, between baseline (no THC) and post-consumption. Although participants' (N = 41) actual hazard perception skill performance did not significantly decline from baseline to post-consumption, their perceived performance did (with no significant correlation between the two in either condition). In the other video-based measures, participants selected significantly slower speeds and longer following distances post-consumption (but gap acceptance behaviour was unchanged). There was no significant change in self-perceptions of driving skills and safety after correction for multiple tests. While there was no evidence that oral ingestion of THC oils by medicinal cannabis users impacted hazard perception skill performance, they were unable to accurately self-assess their performance, regardless of whether they had consumed THC. Further, medicinal cannabis patients engage in compensatory strategies, specifically by reducing their speed and increasing their following distance following the consumption of THC.